Long-term safety and efficacy of glycopyrrolate/formoterol metered dose inhaler using novel Co-Suspension™ Delivery Technology in patients with chronic obstructive pulmonary disease. (May 2017) - Hanania, Nicola A.; Tashkin, Donald P.; Kerwin, Edward M.; Donohue, James F.; Denenberg, Michael; O'Donnell, Denis E.; Quinn, Dean; Siddiqui, Shahid; Orevillo, Chad; Maes, Andrea; Reisner, Colin
Abstract: Background: The long-term safety and efficacy of a novel Co-Suspension™ Delivery Technology glycopyrrolate (GP)/formoterol fumarate (FF) 18/9.6 μg fixed-dose combination metered dose inhaler (GFF MDI) were investigated in a 28-week safety extension study (PINNACLE-3, NCT01970878 ) of two randomized controlled Phase III trials (PINNACLE-1 and -2;NCT01854645 andNCT01854658 ) in subjects with moderate-to-very severe chronic obstructive pulmonary disease (COPD). Methods: Subjects completing 24 weeks' treatment with GFF MDI, GP MDI, FF MDI (all twice-daily) or open-label tiotropium 18 μg (once-daily) in PINNACLE-1 or -2 were randomly selected to continue treatment for 28 weeks. The target enrollment for PINNACLE-3 was 850 subjects. Safety and efficacy were evaluated over 52 weeks. Results: Of 3274 subjects randomized to active treatment in PINNACLE-1 or -2, 892 entered PINNACLE-3. Incidences of adverse events, serious adverse events and major adverse cardiovascular events were similar across treatment groups with no unexpected safety findings. For change from baseline in morning pre-dose trough forced expiratory volume in 1 s (FEV1 ), treatment differences for GFF MDI versus GP MDI, FF MDI and open-label tiotropium over 52 weeks were 57, 65 and 25 mL, respectively (p ≤ 0.0117). Average daily rescue medication use was significantly reduced for GFF MDI versus GP MDI and open-label tiotropium (p ≤ 0.0002). Statistically significant improvements were observed with GFF MDI versus monocomponents in Self-Administered Computerized Transition Dyspnea Index focal score, and in St George's Respiratory Questionnaire total score versus GP MDI. Conclusions: Results confirmed the long-term safety and tolerability of GFF MDI 18/9.6 μg twice-daily in subjects with moderate-to-very severe COPD. Improvements in efficacy endpoints were also sustained over 52 weeks. Highlights: GFF MDI is the first LAMA/LABA fixed dose combination formulated for delivery via MDI. PINNACLE-3 was a 28-week safety extension study of GFF MDI 18/9.6 μg in moderate-to-very severe COPD. Results confirmed the long-term safety and tolerability of GFF MDI 18/9.6 μg BID in COPD. Improvements in efficacy endpoints were sustained over 52 weeks.